IMPLEMENTASI PEMBELAJARAN IPA DENGAN PENDEKATAN STEM UNTUK MENINGKATKAN LITERASI DAN NUMERASI SISWA SEKOLAH DASAR - Rofi'ah, Siti; Patonah, Siti; Sukamto, Sukamto (Jurnal Muara Pendidikan, 2025)
This study examines the application of science learning methods that integrate science, technology, engineering, and mathematics or what is called STEM in grade V students who study sound and light waves. The main objective is to determine the impact of this approach on the Literacy and Numeracy skills of students at Public Elementary School 1 Penganten, Grobogan Regency. The method applied is the pre-test, post test, and pre-experiment method through the one shoot case study design pattern. After being treated with the experimental learning method, the average post-test score of students is significantly influential, namely 85.55 and the pre-test score of students with an average of 43.66 using the PjBL learning method. The results of this study show that there is a difference between the pre-test and post-test results applied in measuring Literacy and Numeracy skills with the STEM approach and the PjBL learning model. The results of the t-test for two dependent samples show that sig <0.05 or 0.000 <0.05. Which means that grade V students at Public Elementary School 1 Penganten have increased their literacy and numeracy scores because they apply the STEM approach